Valuing what matters in Islamic microfinance: Sharia-based ethics and limits of murabahah - Yunita, Anggraeni; Rosalina, Erita; Sumar, Sumar; Wardhani, Rulyanti Susi (Faculty of Economics, Universitas Islam Indonesia, 2026)
Purpose – This study examines the effect of murabahah financing on the net business income of small-scale fishermen in coastal Sumatra and tests whether Sharia value added (SVA), a maqāṣid al-sharīʿah-oriented multidimensional construct, mediates this relationship.Methodology – A structured survey was administered to 310 fishermen selected through clustered sampling across 31 coastal sub-districts in Sumatra. The proposed model was analyzed using partial least squares structural equation modeling (PLS-SEM) to estimate the direct and indirect effects of murabahah implementation, SVA, and net business income.Findings – Murabahah implementation had a positive and significant direct effect on fishermen’s net business income. Murabahah implementation also significantly affected SVA. However, SVA does not have a significant direct effect on net business income. Despite this, the indirect effect of murabahah implementation on income through SVA was statistically significant, indicating the mediating role of SVA. Implications – The results suggest that assessing Islamic microfinance solely through profitability or repayment metrics is insufficient. Evaluation frameworks should incorporate value-based indicators reflected in SVA, such as perceived fairness, ethical orientation, and social benefits, when designing and assessing murabahah-based financing programs for marginalized coastal communities.Originality – This study provides field-based evidence from the fisheries sector by empirically positioning SVA as a mediating mechanism linking murabahah implementation to financial performance, offering a value-oriented perspective that goes beyond procedural contractual compliance.